Spatio-temporal variations of drought in the Welmel watershed, southeast of Ethiopia using the vegetation condition index and standardized precipitation index - Tesfaye Bogale; Sileshi Degefa; Gemedo Dalle; Gebeyehu Abebe (Ecological Processes)
Abstract Background In diverse agroecological settings, determining the magnitude and intensity of drought conditions is crucial for enhancing food security and climate resilience. However, in regions with bimodal agroecology, the specific growing season characterized by frequent and severe droughts remains uncertain. This study aimed to assess the spatiotemporal dynamics of drought in the Welmel watershed in southeastern Ethiopia from 2000 to 2022 using the standard precipitation index (SPI) and vegetation condition index (VCI). The investigation utilized data from the Moderate Resolution Imaging Spectroradiometer and the Climate Hazards Group Infrared Precipitation with Stations, accessed through the Google Earth Engine cloud computing platform. Results The analysis of the SPI and VCI demonstrated that the watershed experienced mild to extreme drought throughout the study period. Between the two growing seasons, March–May (MAM) and September–November (SON), MAM was found to be more susceptible to drought than SON in both indices. The SPI-12 and annual VCI assessments identified 2011, 2019 and 2022 as years with severe and extreme drought events. The spatial distribution of drought severity was more pronounced in lowland regions than in highland regions. The spatial VCI Sen’s slope analysis revealed varied trends, with annual, SON and MAM values decreasing by 1.47, 0.28 and 0.14, respectively. A strong significant correlation was observed between seasonal SPI-3 and MAM VCI (r = 0.68), while the correlation with SON VCI was weak and not statistically significant (r = 0.36). Conclusions This research provides crucial insights for rain-fed agricultural sectors and policymakers, highlighting the importance of the SON growing season in minimizing the potential for drought-related catastrophes in the cultivation of rain-fed crops. In the future, an in-depth examination of the extent of drought in regions with bimodal rainy seasons may prove to be of paramount importance for the agricultural sector and policymakers.